Bilateral hydrometra in a goat - MORE, B K; AMLE, M B; SALUNKHE, S P (The Indian Journal of Animal Reproduction, 2002)
Bilateral hydrometra has been reported in a goat. The histopathological examination of mid portion of both the uterine horns revealed very thin band of reticular fibers with total atrophy of endometrial glands and smooth muscles.